The Age of German idealism - Higgins, Kathleen Marie; Solomon, Robert C. (Routledge history of philosophy, 1993)
German Idealism was one of the most fertile and important movements in the history of Western philosophy. This volume includes eleven chapters on all aspects and the period's most influential philosophers, including Kant and Hegel.